ANTISAPROLEGNIA ACTIVITY OF METHANOLIC EXTRACT OF ZINGIBER OFFICINALE IN BUNNEI (BARBUS SHARPEYI) HATCHERY - Rana H. H. AL-SHAMMARI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Usage of chemicals such as malachite green to disinfect fish eggs in aquaculture has been banned in many countries around the world due to its environmental negative impact. This study aimed to evaluate the Zingiber officinale rhizomes extract as an antifungal agent during incubation period of Bunnei eggs and comparison of its effects with malachite green. For this purpose 24 hours after fertilization, methanolic extract of Zingiber officinale rhizomes in four groups with a concentration of 500, 750, 1000, and 1250 mg/L and three replications per concentration in a (10 minute) bath every 12 hours and malachite green group with a concentration of 0.1 mg/L for (6 minutes) bath was used twice a day and control group without antifungal agents under the same physiochemical conditions as other treatments were tested. The present study showed that the highest percentage of fungal infection was 41.82±0.5 % for the control group and the lowest 0.3±0.5 % was obtained for the treatment of 1250 mg/L of Zingiber officinale rhizomes. Also, the results showed that there were significant differences between treatments of different concentrates of Zingiber officinale rhizomes and with malachite green group in fungal infection, percentage of fertilization and survival do not exist (P>0.05.) No apparent deformity and abnormality were observed in the hatched larvae of Bunnei, so the extract of Zingiber officinale rhizomes with concentration 500 mg /L can be used to disinfect Bunnei eggs during Incubation period and safe material for humans and the environment.